Coping with suicidal urges among youth seen in a psychiatric emergency department. (30th July 2016) - Czyz, Ewa K.; Horwitz, Adam G.; Arango, Alejandra; Cole-Lewis, Yasmin; Berona, Johnny; King, Cheryl A.
Abstract: This study of youth seeking psychiatric emergency department (ED) services examined (1) youth self-efficacy to use suicide-specific coping strategies, (2) whether these self-efficacy beliefs varied by demographic and clinical characteristics, (3) and associations of these beliefs with suicide attempts and ED visits 3–5 months later. Participants were 286 psychiatric ED patients (59% Female), ages 13–25. Ratings of self-efficacy to engage in 10 suicide-specific coping behaviors were assessed at index visit. A total of 226 participants (79%) were assessed 3–5 months later. Youth endorsed low-to-moderate self-efficacy for different suicide-specific coping behaviors, with lowest ratings endorsed for limiting access to lethal means and accessing professional resources. More severe baseline psychopathology was associated with lower self-efficacy. Males endorsed higher self-efficacy for coping behaviors not requiring external support. Lower coping self-efficacy for some of the key strategies, and lower confidence that these strategies will be helpful, differentiated those with and without follow-up suicide attempts and ED visits. The generally low-to-moderate confidence in youths' ability to engage in coping behaviors to manage suicidal crises, and its association with follow-up suicidal crises, is concerning because many of these strategies are commonly included as part of discharge recommendations or safety planning. Implications of findings are discussed. Highlights: Youth seen in psychiatric emergency department at risk for suicide-related events. Suicide-specific coping strategies are often part of discharge or safety planning. Youth reported low confidence in their ability to use these coping strategies. Lower confidence was associated with follow-up suicide attempts and return visits. Attention needed to youths' confidence in ability to use recommended strategies.